2011
DOI: 10.1007/s10333-011-0259-1
|View full text |Cite
|
Sign up to set email alerts
|

Review of SRI modifications in rice crop and water management and research issues for making further improvements in agricultural and water productivity

Abstract: Much of the focus of agricultural improvement efforts in recent decades has been on modifying crops' genetic potential more than on improving cropping practices and production systems. Certainly, this genocentric approach has made significant contributions to food production in certain parts of the world under the banner of ''the Green Revolution.'' Yields have been raised substantially through varietal improvements and the increased use of inputs, including energy, agrochemicals, and delivering more water to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(61 citation statements)
references
References 36 publications
2
59
0
Order By: Relevance
“…Chen et al (2006) attributed the rice yield improvement in SRI to the increased panicles per area. However, Tao and Ma (2003) found that heavy panicles might be the key to the high yield performance in SRI, which was in agreement with the hypothesis that SRI rice plants had an advantage in individual tillers (Kassam et al, 2011;Zhu et al, 2011). Our results indicate that SRI might play an important role in single panicle development in MT and TP, which provided evidence for the importance of a strong individual tiller.…”
Section: Tillering Characteristicssupporting
confidence: 55%
See 2 more Smart Citations
“…Chen et al (2006) attributed the rice yield improvement in SRI to the increased panicles per area. However, Tao and Ma (2003) found that heavy panicles might be the key to the high yield performance in SRI, which was in agreement with the hypothesis that SRI rice plants had an advantage in individual tillers (Kassam et al, 2011;Zhu et al, 2011). Our results indicate that SRI might play an important role in single panicle development in MT and TP, which provided evidence for the importance of a strong individual tiller.…”
Section: Tillering Characteristicssupporting
confidence: 55%
“…The positive effect of SRI on TP rice has been well documented (Stoop et al, 2002;Lin et al, 2005;Kassam et al, 2011;Zhu et al, 2011). In the current study, similar results were found in the TP and MT systems.…”
Section: Tillering Characteristicsmentioning
confidence: 90%
See 1 more Smart Citation
“…The rapid growth of the Internet, through e-mail and websites, and more recently social media, helped the spread of SRI across the world with continuous adaptation. An estimated 10 million farmers across 50 countries have experimented with many or all SRI principles on more than 4 million hectares (Kassam et al 2011. Most of the spread of SRI has been from five Asian countries-China, India, Vietnam, Indonesia, and Cambodia.…”
Section: Spread Of the System Of Rice Intensification In India: Sociamentioning
confidence: 99%
“…These papers invited responses from the SRI community (Stoop and Kassam 2005;Uphoff et al 2008;Stoop et al 2009;Kassam et al 2011). Especially claims of very high yields, yields that went beyond what is considered the yield potential for rice, raised much commentary.…”
Section: Box 11 the Sri Controversymentioning
confidence: 99%